Maximum and Minimum Temperature Trends Variation over Northern and Southern Part of Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
Temperature is one of the pivotal climatic variables in our world climate literature. In the present study monthly, seasonal and yearly highest maximum and lowest minimum temperatures of two cities were analyzed. Mann-Kendall test and Sens Slope Estimator were used to determine the trend and slope magnitude. Chittagong, as the coastal city and Rajshahi, as Barind track were selected as a study area due to its respective geographical location. Such types of data of 52 years for Chittagong as well as 48 years for Rajshahi were collected from Bangladesh Meteorological Department (BMD). Monthly highest maximum and lowest minimum temperature data from 1950-2002 for Chittagong and 1964-2012 for Rajshahi were used for analysis. In Rajshahi, significant rising trends were found in highest maximum post-monsoon temperature, lowest minimum monsoon temperature and highest maximum temperature from July to October, June and August for lowest minimum temperature. Falling trends were found in annual highest maximum and lowest minimum temperatures, pre-monsoon highest maximum temperature, lowest minimum winter temperature and January lowest minimum temperature. For Chittagong, significant increasing trends found in post-monsoon highest maximum temperature, June to December highest maximum temperature except July and December lowest minimum temperature. No significant decreasing trend was found in Chittagong.DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22101 J. Environ. Sci. & Natural Resources, 6(2): 83-88 2013